Factors that influence employee using electronic system (e-system) (case study with resident office of Betong) / Rohani Sejeli - Sejeli, Rohani (2007)
Following rapid economic and social advancement, Malaysia has placed a great emphasis on Information and Communication Technology (ICT) particularly on the development of a knowledge management such as e-govemment and k-society. In the wake of new technologies and electronic based activities, there has arisen an enhanced need for evaluating program to look forward the successfulness of the system in the respective organizations.